KARAKTERISTIK PAPAN PARTIKEL CAMPURAN SERBUK GERGAJIAN KAYU SENGON DAN KULIT BUAH KOPI DENGAN PEREKAT DEKSTRIN TEPUNG ONGGOK - Nurannisa Syafitri; Auliya Shafiah Zakhrakh; Syifa Nur Annissa; Sutrisno; Eka Mulya Alamsyah; Tati Karliati; Jamaludin Malik (BRIN Publishing, 2022)
Waste from forest and agricultural products currently does not have good economic value, so the manufacture of particle boardcould be a solution. The objective of this research is to obtain the physical and mechanical characteristics of particle board fromsengon wood sawdust and coffee bean bark using cassava flour waste-based dextrin adhesive. Dextrin was manufactured by spraying5 mL of 5% HCl to 80 g cassava flour waste starch, then heated at 130°C for 3 hours. Particle board manufactured with targetof density 0.6 g/cm3. To obtain the optimal composition of materials mixture, the particleboards were made with 4 compositions,based on the weight ratio between sengon wood sawdust and coffee fruit bark; 100%:0%, 75%:25%, 50%:50%, and 25%:75%.The dextrin adhesive used is 20% based on dry kiln weight of the particles and hot-pressing was conducted at a temperature of185°C and pressured 20 kgf/cm2for 10 minutes. The physical properties test showed that the density 0.490.64 g/cm3, moisturecontent 7.89%9.01%, water absorption 92.41167.65%, and thickness swelling 11.31%59.9%. Particle board withmixture composition of 25% sengon wood sawdust and 75% coffee fruit bark was fulfilled the physical properties: density, moisturecontent, and thickness swelling, while water absorption value did not specify in the JIS A 5908: 2003 standard. Mechanicalproperties test showed that the internal bond value was 0.020.03 N/mm2 and resistance to screw withdrawal value was46.4144 N. Particle board with a mixture of 25% sengon wood sawdust and 75% coffee fruit bark has the optimum mechanicalproperties, however it did not meet the JIS A 5908: 2003 standard.